2019
DOI: 10.1063/1.5063797
|View full text |Cite
|
Sign up to set email alerts
|

Electromigration in the dissipative state of high-temperature superconducting bridges

Abstract: Increased energy efficiency spin-torque switching of magnetic tunnel junction devices with a higher order perpendicular magnetic anisotropy Applied Physics Letters 114, 012404 (2019);

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…One particularly appealing aspect that could situate voltage-controlled electromigration as a privileged tool of choice for tuning the oxygen content is the possibility to heal a previously electromigrated sample, by simply inverting the direction of the electrical drive (antielectromigration). Although this technique seems to work fairly well for elemental materials, its success in YBCO has been shown to be rather limited . In order to illustrate this effect, starting from the EM sample (inset of Figure b) we invert the polarity of the voltage in such a way that now the right bridge corresponds to the cathode side and the left bridge to the anode side.…”
Section: Results and Discussionmentioning
confidence: 99%
“…One particularly appealing aspect that could situate voltage-controlled electromigration as a privileged tool of choice for tuning the oxygen content is the possibility to heal a previously electromigrated sample, by simply inverting the direction of the electrical drive (antielectromigration). Although this technique seems to work fairly well for elemental materials, its success in YBCO has been shown to be rather limited . In order to illustrate this effect, starting from the EM sample (inset of Figure b) we invert the polarity of the voltage in such a way that now the right bridge corresponds to the cathode side and the left bridge to the anode side.…”
Section: Results and Discussionmentioning
confidence: 99%
“…A resistance R max is measured at the top of the excitation pulse starting 1 ms after the rising edge of the pulse, and a resistance R min is recorded at the top of the probe pulse. A similar protocol has been used in [15,33]. At low I max values, R max ≈R min (see figure 2).…”
Section: Measurement Protocol and Criterion For Em Breakdownmentioning
confidence: 99%
“…Later on, Schirm and co-authors [30] used EM to toggle the conductance of an aluminum atomic contact between two well-defined values in the range of a few conductance quanta. More recently, the concept of EM-stimulated resistance switching has been applied to cluster-assembled gold films by Minnai et al [31] and remains a promising approach in current-controlled oxygen doping in YBa 2 Cu 3 O 7−δ [32,33]. Interestingly, the threshold logic implemented by memristive devices permits to emulate synaptic actions in which the memristance of the device can be incrementally modified and a thresholding system governs the firing of the output [34,35].…”
Section: Introductionmentioning
confidence: 99%
“…Such control can be achieved electrically, via the application of currents or voltages. One of the possible oxygen-control approach consists of circulating large current densities, as reported in thin films and nanoconstrictions [30][31][32][33][34][35]. In these experiments, it was shown that a sufficiently large current (typically above 7 MA • cm −2 ) [33][34][35][36] can produce direct electromigration of the different atomic species.…”
Section: Introductionmentioning
confidence: 99%